Ceramic coating with excellent wear resistance as well as preparation method and application thereof

By using a ceramic coating composed of Ti, Mo, B, and N elements, nanotwinned and amorphous structures were prepared using DC magnetron sputtering technology. This solved the problem of poor toughness in hard coatings and achieved high wear resistance and self-lubricating effect, making it suitable for surface protection of rotating components in nuclear power plants.

CN121046799APending Publication Date: 2025-12-02UNIV OF SCI & TECH BEIJING +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511177428.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing hard coatings have high hardness but poor toughness, which makes them prone to cracking and crack propagation in nuclear power plant service environments, making it difficult to meet wear resistance requirements.

Method used

A ceramic coating composed of Ti, Mo, B, and N elements is deposited twice using DC magnetron sputtering technology to form a nanotwinned structure and an amorphous structure. Combined with the self-lubricating phase MoO3 of Mo, the strength and toughness of the coating are improved.

Benefits of technology

It significantly improves the wear resistance and toughness of the coating, reduces the coefficient of friction, enhances chemical stability under high temperature and chemical corrosion environments, and extends the service life of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121046799A_ABST
    Figure CN121046799A_ABST
Patent Text Reader

Abstract

The invention provides a ceramic coating with excellent wear resistance and a preparation method and application thereof, and relates to the technical field of ceramic coating preparation, the ceramic coating is composed of Ti, Mo, B and N. The content range of the Mo element is 16.1-36.8 at.%. The invention also provides a preparation method of the ceramic coating. The preparation method comprises the following steps: cleaning the substrate; argon is introduced, the power of the Ti target is adjusted, and first deposition is carried out; and argon and nitrogen are introduced, the TiB2 target, the Ti target and the Mo target are opened, secondary deposition is carried out on the substrate coated with the Ti transition layer, the flow of the nitrogen is 5.2-7.2 sccm, the bias voltage of the substrate is-140-80 V in the secondary deposition process, and the high-wear-resistance ceramic coating is obtained. The high-wear-resistance ceramic coating disclosed by the invention has relatively good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic coating preparation technology, specifically to a ceramic coating with excellent wear resistance, its preparation method, and its application. Background Technology

[0002] With the rapid development of modern industry, wear failure has become a significant threat to the service life of engineering equipment in many engineering fields. According to incomplete statistics, from 1996 to 2021, rotating components such as pump shafts, impellers, and valve stems in CGN's power plants experienced wear problems exceeding 10,000 times. Insufficient wear resistance of component surfaces is the main cause of component failure, leading to a sharp reduction in service life and increased maintenance and replacement costs. Surface protection is an effective way to improve the hardness and wear resistance of materials without changing the base material, such as hard wear-resistant coating technology. Developing hard wear-resistant coatings is a highly effective method to mitigate wear failure in rotating components of nuclear power plants. To improve the wear resistance of coatings, the key is to increase the coating's hardness and toughness while reducing its elastic modulus and coefficient of friction. Currently, some research and development on hard coatings has been conducted, such as multi-component composite coatings like TiAlN, CrAlN, and TiCrAlN, which typically achieve a hardness of 30-50 GPa. Chinese patent CN115181948A, published under publication number CN115181948A, uses DC magnetron sputtering technology to prepare a W-Si-B hard coating with a hardness exceeding 35 GPa and excellent tribological properties (wear rate as low as 1.3 × 10⁻⁶). 7mm 3 Wear-resistant hard coatings (approximately 0.5 Nm) are applied to the surface protection of cutting tools or workpieces, effectively extending their service life. While these coatings possess high hardness, their poor toughness remains a persistent problem, leading to easy cracking and crack propagation, falling far short of the requirements of nuclear power plant service environments. Therefore, developing wear-resistant hard coatings with both high strength and high toughness is an urgent problem to be solved in the surface protection engineering of components in service in fields such as nuclear power. Summary of the Invention

[0003] This invention provides a ceramic coating with excellent wear resistance, its preparation method and application, to solve the technical problem of high hardness but poor wear resistance of metal coatings in the prior art.

[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A ceramic coating with excellent wear resistance, wherein the ceramic coating contains Ti, Mo, B and N elements, wherein the content of Mo element ranges from 16.1 to 36.8 at.

[0005] A method for preparing a ceramic coating with excellent wear resistance according to the present invention includes the following steps: S1. After heating the substrate, place it into the vacuum chamber of a DC magnetron sputtering equipment, adjust the vacuum level, introduce argon gas, and perform glow discharge cleaning to obtain the substrate. S2. Argon gas is introduced, the Ti target power is adjusted, and magnetron sputtering technology is used to perform the first deposition to deposit a Ti transition layer on the substrate, thereby obtaining a substrate covered with a Ti transition layer. S3. Introduce argon and nitrogen gas, turn on the TiB2 target, Ti target and Mo target, and perform a second deposition on the substrate covered with the Ti transition layer. During the second deposition, the nitrogen flow rate is 5.2-7.2 sccm. After cooling, the ceramic coating with excellent wear resistance is obtained.

[0006] Preferably, the heating temperature in S1 is 350-480°C.

[0007] Preferably, the glow discharge cleaning time in S1 is 10-20 min.

[0008] Preferably, the power of the first Ti target deposition in S2 is 340-480W, and the flow rate of the introduced argon gas is 20-25sccm.

[0009] Preferably, the temperature of the first deposition in S2 is 350-480℃, and the time of the first deposition is 8-10 min.

[0010] Preferably, the thickness of the Ti transition layer in S2 is 80-100 nm.

[0011] Preferably, the power of the second deposition TiB2 target in S3 is 80-85W, the power of the second deposition Ti target is 400-450W, and the power of the second deposition Mo target is 120-180W.

[0012] Preferably, the temperature of the second deposition in S3 is 350-480℃, and the time of the second deposition is 3-4 hours.

[0013] The application of a ceramic coating with excellent wear resistance as described in this invention in pump shafts, impellers and / or valve stems of rotating components in nuclear power plants.

[0014] This invention prepares a ceramic coating with excellent wear resistance through a two-stage deposition process, incorporating nanotwins in its structure. The parameters for the second deposition, such as the power of the TiB2 target, Ti target, and Mo target, nitrogen flow rate, substrate bias, and deposition temperature, serve two purposes: first, to ensure the stable existence of the nanotwin structure within the ceramic coating; and second, to control the grain size of the coating by adjusting the Mo atomic ratio, primarily through adjusting the power of the Mo target. Firstly, ensuring the introduction of nanotwins into the ceramic coating system is crucial. Nanotwins are a structure that can simultaneously improve the strength and toughness of materials. The twin interfaces generated by the twins hinder and absorb dislocation movement, while also increasing the crack propagation path, significantly improving fracture toughness. The coating structure of this invention also contains a large number of amorphous structures. Since amorphous structures do not contain grain boundaries and dislocations, amorphization is also an effective way to improve material strength. Amorphous materials themselves lack a long-range ordered lattice structure; their atomic arrangement is random. During stress, the amorphous phase can absorb stress through local atomic rearrangement. This disordered atomic arrangement and stress relaxation mechanism typically lead to a lower elastic modulus. Secondly, different amounts of Mo were incorporated to ensure that the addition of Mo did not affect the stable existence of the twinned structure. Mo exists in the coating as a (Ti,Mo)N substitution solid solution, while B remains in an amorphous phase, and the coating maintains the fcc-TiN structure. Simultaneously, the high Mo content leads to grain refinement. At a high Mo content (36.8 at.%), the friction coefficient of the coating decreases to approximately 0.25 due to the formation of a self-lubricating Magnéli phase MoO3 through Mo frictional reaction. Combining the nanotwinned phase and the mechanism of Mo frictional reaction to generate the self-lubricating Magnéli phase MoO3 results in a composite material with high strength and low elastic modulus, i.e., an increased H / E ratio, thus significantly improving the material's wear resistance.

[0015] The technical solution of the present invention has at least the following beneficial effects compared with the prior art: The Ti-N, Mo-N, BN, Ti-B, and Mo-B bonds in the Ti-Mo-BN ceramic coating structure of this invention are high-strength covalent bonds, ensuring the high hardness and wear resistance of the ceramic coating. The high binding energy of these bonds not only imparts significant mechanical hardness to the coating but also ensures its chemical stability under high temperature and chemical corrosion environments. Furthermore, Mo atoms are introduced into the coating. The incorporation of Mo atoms has two effects: low Mo content increases the coating grain size, while higher Mo content gradually reduces the grain size. This grain refinement and solid solution strengthening mechanism increase the coating hardness. Additionally, the Mo friction reaction generates a self-lubricating Magnéli phase MoO3. Simultaneously, the nanotwinned structure in the coating transforms the wear mechanism from a combination of abrasive wear, brittle spalling, and microcracks into uniform wear. This significantly improves the wear resistance of the coating. The combination of the self-lubricating Magnéli phase MoO3 and the nanotwinned structure significantly enhances the wear resistance of the ceramic coating. Furthermore, by first depositing a Ti transition layer on the substrate and precisely controlling the gas flow rate and substrate bias during magnetron sputtering, the uniformity and adhesion of the final coating were ensured, and the prepared metal coating exhibited exceptionally good wear resistance. Attached Figure Description

[0016] Figure 1 This is a cross-sectional morphology diagram of a ceramic coating with excellent wear resistance prepared in Example 1; Figure 2 The diffraction pattern is shown for a ceramic coating with excellent wear resistance prepared in Example 1. Figure 3 This is an EDS surface scan composition diagram of a ceramic coating with excellent wear resistance prepared in Example 1; Figure 4 This is a cross-sectional morphology diagram of a ceramic coating with excellent wear resistance prepared in Example 2; Figure 5 The diffraction pattern is shown for a ceramic coating with excellent wear resistance prepared in Example 2. Figure 6 This is a cross-sectional morphology diagram of a ceramic coating with excellent wear resistance prepared in Example 3; Figure 7 This is a cross-sectional morphology diagram of the ceramic coating prepared in Comparative Example 1; Figure 8 The diffraction pattern of the ceramic coating prepared in Comparative Example 2 is shown. Figure 9 The image shows the SEM image of the worn surface of the ceramic coating with excellent wear resistance prepared in Example 1 after wear. Figure 10 The image shows the three-dimensional morphology of the worn surface and the wear track depth curve of the ceramic coating with excellent wear resistance prepared in Example 1 after damage. Figure 11 The image shows the SEM image of the worn surface of the ceramic coating with excellent wear resistance prepared in Example 2 after wear. Figure 12 The image shows the three-dimensional morphology of the worn surface and the wear track depth curve of the ceramic coating with excellent wear resistance prepared in Example 2 after wear. Figure 13 The image shows the SEM image of the worn surface of the ceramic coating with excellent wear resistance prepared in Example 3 after wear. Figure 14 The image shows the three-dimensional morphology of the worn surface and the wear track depth curve of the ceramic coating with excellent wear resistance prepared in Example 3 after wear. Figure 15 The image shows a SEM image of the worn surface of the ceramic coating prepared in Comparative Example 1 after wear. Figure 16 The image shows the three-dimensional morphology of the worn surface and the wear track depth curve of the ceramic coating prepared in Comparative Example 1 after wear. Figure 17 Here is a SEM image of the worn surface of the ceramic coating prepared in Comparative Example 2 after wear. Figure 18 The image shows the three-dimensional morphology of the worn surface and the wear track depth curve of the ceramic coating prepared in Comparative Example 2 after wear. Figure 19 The image shows a cross-sectional SEM image of the wear marks on the ceramic coating with excellent wear resistance prepared in Example 2. Figure 20 This is a selected area diffraction pattern of the cross-section of the ceramic coating with excellent wear resistance prepared in Example 2; Figure 21 for Figure 19 The ITB structure diagram within the middle circle; Figure 22 for Figure 21 HTEM image of the ITB structure in the image. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0018] Example 1

[0019] This embodiment provides a method for preparing a ceramic coating with excellent wear resistance, including the following steps: S1. Place the pretreated substrate into the vacuum chamber of the DC magnetron sputtering equipment, and start the mechanical pump, molecular pump, etc. to evacuate the chamber; wait until the vacuum level in the chamber reaches 2×10⁻⁶. -3 When the temperature is below Pa, the substrate is heated and rotated by increasing the temperature to 350°C at a rate of 10°C / min. S2. After heating the substrate, place it into the vacuum chamber of the DC magnetron sputtering equipment, and adjust the vacuum level of the vacuum chamber to 2×10⁻⁶. -3 Pa, argon gas is introduced to make the pressure in the vacuum chamber 0.3 Pa, and then the base bias is turned on to -900V to make the argon gas glow discharge and perform glow cleaning for 10 min. S3. Argon gas is introduced, the Ti target power is adjusted, and magnetron sputtering technology is used to perform the first deposition. The deposition temperature is 350℃ and the time is 10min. During the deposition process, the Ti target power is 480W and the argon gas flow rate is 20sccm. A Ti transition layer with a thickness of 100nm is deposited on the substrate to obtain a substrate covered with a Ti transition layer. S4. Argon and nitrogen are introduced, and the TiB2 target, Ti target, and Mo target are turned on. A second deposition is performed on the substrate covered with the Ti transition layer. The deposition temperature is 350℃ and the time is 3h. During the second deposition, the nitrogen flow rate is 5.2sccm, the substrate bias voltage is -110V, the power of the TiB2 target is 80W, the power of the Ti target is 450W, and the power of the Mo target is 120W. After cooling, the ceramic coating with excellent wear resistance is obtained.

[0020] This embodiment presents a ceramic coating with excellent wear resistance. The ceramic coating contains Ti, Mo, B, and N elements, and the atomic percentage of Mo in the ceramic coating is 16.1 at.%. Its cross-sectional morphology is as follows: Figure 1 As shown, the diffraction pattern is as follows Figure 2 As shown, SEM surface scan Figure 3 As shown, Figure 3 It can be seen that the ceramic coating contains Ti, Mo, B, and N elements.

[0021] Example 2

[0022] This embodiment provides a method for preparing a ceramic coating with excellent wear resistance, including the following steps: S1. Place the pretreated substrate into the vacuum chamber of the DC magnetron sputtering equipment, and start the mechanical pump, molecular pump, etc. to evacuate the chamber; wait until the vacuum level in the chamber reaches 2×10⁻⁶. -3 When the temperature is below Pa, the substrate is heated and rotated by increasing the temperature to 400℃ at a rate of 10℃ / min. S2. After heating the substrate, place it into the vacuum chamber of the DC magnetron sputtering equipment, and adjust the vacuum level of the vacuum chamber to 2×10⁻⁶. -3 Pa, argon gas is introduced to make the pressure in the vacuum chamber 0.3 Pa, and then the base bias is turned on to -800V to make the argon gas glow discharge and perform glow cleaning for 20 min; S3. Argon gas is introduced, the Ti target power is adjusted, and magnetron sputtering technology is used to perform the first deposition. The deposition temperature is 400℃ and the time is 9min. During the deposition process, the Ti target power is 410W and the argon gas flow rate is 21 sccm. A Ti transition layer with a thickness of 81nm is deposited on the substrate to obtain a substrate covered with a Ti transition layer. S4. Argon and nitrogen gas are introduced, and the TiB2 target, Ti target, and Mo target are turned on. A second deposition is performed on the substrate covered with the Ti transition layer. The deposition temperature is 400℃ and the time is 3.5h. During the second deposition, the nitrogen flow rate is 6.2sccm, the substrate bias voltage is -110V, the power of the TiB2 target is 84W, the power of the Ti target is 400W, and the power of the Mo target is 150W. After cooling, the ceramic coating with excellent wear resistance is obtained.

[0023] This embodiment presents a ceramic coating with excellent wear resistance. The molecular form of the ceramic coating is TiMoBN, and the atomic percentage of Mo in the ceramic coating is 24.5 at.%. Its cross-sectional morphology is as follows: Figure 4 As shown, the diffraction pattern is as follows Figure 5 As shown.

[0024] Example 3

[0025] This embodiment provides a method for preparing a ceramic coating with excellent wear resistance, including the following steps: S1. Place the pretreated substrate into the vacuum chamber of the DC magnetron sputtering equipment, and start the mechanical pump, molecular pump, etc. to evacuate the chamber; wait until the vacuum level in the chamber reaches 2×10⁻⁶. -3 When the temperature is below Pa, the substrate is heated and rotated by increasing the temperature to 480°C at a rate of 10°C / min. S2. After heating the substrate, place it into the vacuum chamber of the DC magnetron sputtering equipment, and adjust the vacuum level of the vacuum chamber to 2×10⁻⁶. -3 Pa, argon gas is introduced to make the pressure in the vacuum chamber 0.3 Pa, and then the base bias is turned on to -800V to make the argon gas glow discharge and perform glow cleaning for 18 min; S3. Argon gas is introduced, the Ti target power is adjusted, and magnetron sputtering technology is used to perform the first deposition. The deposition temperature is 480℃ and the time is 8min. During the deposition process, the Ti target power is 340W and the argon gas flow rate is 25 sccm. A Ti transition layer with a thickness of 80nm is deposited on the substrate to obtain a substrate covered with a Ti transition layer. S4. Argon and nitrogen are introduced, and the TiB2 target, Ti target, and Mo target are turned on. A second deposition is performed on the substrate covered with the Ti transition layer. The deposition temperature is 480℃ and the time is 4h. During the second deposition, the nitrogen flow rate is 7.2sccm, the substrate bias voltage is -110V, the power of the TiB2 target is 85W, the power of the Ti target is 410W, and the power of the Mo target is 180W. After cooling, the ceramic coating with excellent wear resistance is obtained.

[0026] This embodiment presents a ceramic coating with excellent wear resistance. The molecular form of the ceramic coating is TiMoBN, and the atomic percentage of Mo in the ceramic coating is 36.8 at.%. Its cross-sectional morphology is as follows: Figure 6 As shown.

[0027] Comparative Example 1

[0028] The preparation method in this comparative example is similar to that in Example 1, except that the Mo target power in S4 of this comparative example is 60W, and the atomic percentage of Mo in the ceramic coating prepared in this comparative example is 3.6 at.%, and its cross-sectional morphology is as follows. Figure 7 Show.

[0029] Comparative Example 2

[0030] The preparation method in this comparative example is similar to that in Example 2, except that the N2 flow rate in S4 in this comparative example is 8.2 sccm. The diffraction pattern of the ceramic coating prepared in this comparative example is shown below. Figure 8 As shown.

[0031] The ceramic coatings prepared in Examples 1, 2, and 3, and Comparative Examples 1 and 2 were subjected to wear surface morphology and wear track width tests. The test results are as follows: Figures 9 to 18 As shown. Figure 9 This is a SEM image of the worn surface of the ceramic coating with excellent wear resistance prepared in Example 1 after wear. Figure 10 The image shows the three-dimensional morphology of the worn surface and the wear track depth curve of the ceramic coating with excellent wear resistance prepared in Example 1 after wear. Figure 11 This is a SEM image of the worn surface of the ceramic coating with excellent wear resistance prepared in Example 2 after wear. Figure 12Image 13 shows the three-dimensional morphology and wear track depth curve of the worn surface of the ceramic coating with excellent wear resistance in Example 2 after wear; Image 14 shows the SEM image of the worn surface of the ceramic coating with excellent wear resistance prepared in Example 3 after wear. Figure 14 The image shows the three-dimensional morphology of the worn surface and the wear track depth curve of the ceramic coating with excellent wear resistance in Example 3 after wear. Figure 15 This is a SEM image of the worn surface of the ceramic coating prepared in Comparative Example 1 after wear. Figure 16 The image shows the three-dimensional morphology of the worn surface and the wear track depth curve of the ceramic coating prepared in Comparative Example 1 after wear. Figure 17 This is a SEM image of the worn surface of the ceramic coating prepared in Comparative Example 1 after wear. Figure 18 The image shows the three-dimensional morphology of the worn surface and the wear depth curve of the ceramic coating prepared in Comparative Example 1 after wear.

[0032] It can be seen that the ceramic coatings in Comparative Examples 1 and 2 have obvious wear marks. The maximum wear mark width of the coating prepared in Example 1 is 354.6 μm, the maximum wear mark width of the coating prepared in Example 2 is 308.2 μm, and the maximum wear mark width of the coating in Example 3 is 324.4 μm, which are much smaller than the maximum wear mark widths of 708.4 μm and 578.7 μm of the samples in Comparative Examples 1 and 2, respectively.

[0033] The extremely poor wear resistance in Comparative Example 1 is attributed to its low Mo content. Low Mo content increases the coating grain size; at a Mo content of 3.6 at.%, the damage mechanism of the coating is a coupling of abrasive wear and brittle spalling. Mo's excellent self-lubricating properties allow the coating's damage mechanism to shift to a more favorable abrasive wear. When the Mo content in the coating increases to 16.1 at.%, the damage mechanism is solely abrasive wear. When the Mo content in the coating increases to 24.5 at.%, the oxides (MoO3, TiO2, or B2O3) primarily generated by wear have good anti-friction and lubricating effects, helping to reduce coating wear. For hard coatings, abrasive wear is a relatively superior wear mechanism, leveraging the wear resistance advantage of high-hardness coatings, and the resulting wear loss is far less than the loss caused by coating spalling.

[0034] The poor wear resistance in Comparative Example 2 was attributed to the low twin ratio caused by excessive nitrogen flow during the coating process. Introducing a nanotwin structure can also transform the wear mechanism of the coating from a combination of abrasive wear, brittle spalling, and microcracks to uniform wear, thereby improving the wear resistance of the coating.

[0035] Structural analysis was performed on the subsurface layer of the ceramic coating with excellent wear resistance in Example 2 after wear. The cross-sectional SEM image of the wear track is shown below. Figure 19 As shown, the selected area diffraction pattern of the cross section is as follows: Figure 20 As shown, Figure 19The ITB structure in the white circle is as follows Figure 21 As shown, Figure 21 HTEM diagram of the ITB structure in the image is as follows Figure 22 As shown, nanotwins still exist in the subsurface layer of the coating after wear, and the highly stable nanotwins maintain high surface hardness. The introduction of the nanotwin structure changes the wear mechanism of the coating from a combination of abrasive wear, brittle spalling, and microcracks to uniform wear, thereby greatly improving the wear resistance of the coating.

[0036] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. The scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A ceramic coating with excellent wear resistance, characterized in that, The ceramic coating contains Ti, Mo, B, and N elements, wherein the content of Mo ranges from 16.1 to 36.8 at.%.

2. A method for preparing a ceramic coating with excellent wear resistance as described in claim 1, characterized in that, Includes the following steps: S1. After heating the substrate, place it into the vacuum chamber of a DC magnetron sputtering equipment, adjust the vacuum level, introduce argon gas, and perform glow discharge cleaning to obtain the substrate. S2. Argon gas is introduced, the Ti target power is adjusted, and magnetron sputtering technology is used to perform the first deposition to deposit a Ti transition layer on the substrate, thereby obtaining a substrate covered with a Ti transition layer. S3. Introduce argon and nitrogen gas, turn on the TiB2 target, Ti target and Mo target, and perform a second deposition on the substrate covered with the Ti transition layer. During the second deposition, the nitrogen flow rate is 5.2-7.2 sccm. After cooling, the ceramic coating with excellent wear resistance is obtained.

3. The preparation method according to claim 2, characterized in that, The heating temperature described in S1 is 350-480℃.

4. The preparation method according to claim 2, characterized in that, The glow discharge cleaning time described in S1 is 10-20 min.

5. The preparation method according to claim 2, characterized in that, The power of the first Ti target deposition described in S2 is 340-480W, and the flow rate of the introduced argon gas is 20-25sccm.

6. The preparation method according to claim 2, characterized in that, The temperature for the first deposition, as described in S2, is 350-480℃, and the deposition time is 8-10 minutes.

7. The preparation method according to claim 2, characterized in that, The thickness of the Ti transition layer in S2 is 80-100 nm.

8. The preparation method according to claim 2, characterized in that, The power of the second TiB2 target deposition in S3 is 80-85W, the power of the second Ti target deposition is 400-450W, and the power of the second Mo target deposition is 120-180W.

9. The preparation method according to claim 2, characterized in that, The temperature for the second deposition described in S3 is 350-480℃, and the deposition time is 3-4 hours.

10. The application of a ceramic coating with excellent wear resistance as described in claim 1 in pump shafts, impellers and / or valve stems of rotating components in nuclear power plants.

Citation Information

Patent Citations

  • W-Si-B hard coating and preparation method and application thereof

    CN115181948A